Effect of a 12-week submaximal swimming training in rats exposed to tobacco- derived nitrosamine ketone - Ali Barzegari; Shadmehr Mirdar (Babol University of Medical Sciences, 2018)
Background: Tobacco contains carcinogens such as NNK (nicotine-derived nitrosamine ketone) that makes induction of lung cancer by changing the stimulation of IL-10 expression. The aim of this study was to investigate changes in resting levels of IL-10 in lung tissues of rats exposed to NNK after a 12-week aerobic submaximal swimming training. Methods: For this purpose, 46 Wistar rats were randomly divided into five groups consisting training, training + NNK, NNK, saline and control. NNK-induced groups received NNK subcutaneously one day per week at a rate of 12/5 mg per kg body weight and the training groups performed submaximal swimming training for 12 weeks. The levels of IL-10 in homogenized lung tissue were measured by ELISA. Results: Findings indicated that a period of swimming training increased the IL-10 levels significantly in lung tissue of training group when compared to control (P=0.00) and NNK groups (P=0.00). Also, a significant increase of IL-10 level was observed in exercise + NNK group when compared to NNK group (p≤0/02). Furthermore, it was observed that IL-10 levels of NNK group had a significant decrease when compared to training group (P=0/00), training + NNK group (p≤0/02), but had insignificant increase when compared to saline group (p≤0/85). Conclusions: Generally, it could be confirmed that regular submaximal aerobic training plays an important role in the inhibition of the effects of lung inflammation induced by NNK via increasing IL-10 activity.